2005
DOI: 10.1177/000348940511400908
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Gel for Endoscopic Sinus Surgery

Abstract: Platelet gel used as a packing material after endoscopic sinus surgery offers efficient hemostatic properties, as well as growth factors that can advance the healing process. The quality of life of the patient may be improved by the use of platelet gel packing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 10 publications
0
43
0
1
Order By: Relevance
“…In their study, none of the patients showed postoperative bleeding that required packing. 17 To date, no conclusive evidence has been obtained for an optimal packing material that is superior to all the others with respect to prevention of postoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, none of the patients showed postoperative bleeding that required packing. 17 To date, no conclusive evidence has been obtained for an optimal packing material that is superior to all the others with respect to prevention of postoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported no postoperative bleeding in either arm of the study. 11 Similarly, in a study by Baumann et al (level 2 evidence), the incidence of postoperative bleeds was calculated and they did not find a difference between FloSeal (1/50) and Merocel (2/50). 7 Vaiman et al took a different perspective on postoperative bleeds and calculated into the equation the bleeding caused by pulling Merocel packs.…”
Section: Middle Meatal Packing For Hemostasismentioning
confidence: 96%
“…These authors suggest that the use of PLG contributed to an enhanced hemostatic response, accelerated tissue healing, and improved collagen synthesis, thus preventing anastomotic leaks and thereby improving outcome. Recently, Pomerantz and Dutton [33] applied PLG during endoscopic sinus surgery to improve their packing technique. Their quality-of-life scores showed an improvement in terms of postoperative epistaxis, synechia formation, and exuberant granulation tissue in PLG-treated patients.…”
Section: Soft Tissue Healing and Endoscopic Applicationsmentioning
confidence: 99%